Correlations between bladder wall thickness and clinical manifestations in female patients with detrusor underactivity and detrusor overactivity–with–detrusor underactivity. Issue 10 (31st August 2021) - Yu, Ping-Hsuan; Lin, Chih-Chieh; Fan, Yu-Hua; Lin, Alex T. L.; Huang, William J. S.
Abstract : Background: Among female patients with lower urinary tract symptoms, detrusor underactivity (DU), and detrusor overactivity–with–detrusor underactivity (DO-DU) are two common diagnoses. Here, we investigated the correlations between bladder wall thickness (BWT) and clinical manifestations of the two diagnoses. Methods: From 2011 to 2016, female patients with DU or DO-DU, diagnosed at our institute, were recruited. We analyzed their urodynamic parameters and collected three questionnaires (IPSS, UDI-6, OABSS). Using transabdominal sonography, the BWT was recorded. DU was defined as follows: maximum free flow rate ( Q max ) ≤ 15 cc/s; detrusor pressure at maximum flow ( P detQmax ) ≤ 20 cmH2 O; bladder capacity > 150 cc. DO-DU was defined as follows: Q max ≤ 15 cc/s; P detQmax ≤ 20 cmH2 O; bladder capacity ≤ 150 cc. The BWTs of the two groups were compared using the Mann–Whitney U test; the correlations among the BWTs and the results of three questionnaires were analyzed using Spearman's rank correlation coefficient. Results: Forty-eight female patients with DU and 13 with DO-DU were recruited. Demographic data revealed no differences between the two groups. The mean BWT of the DO-DU patients was significantly larger than that of the DU patients (4.11 vs 3.42 mm; p = 0.001). In the DO-DU group, a high correlation existed between the BWT and some of the UDI-6 items (urgency incontinence: r = 0.831, p = 0.006; incontinence related to activity: r = 0.884, p = 0.002; small amounts of leakage: r = 0.809, p = 0.008). The BWT of the DO-DU patients also exhibited a moderate correlation with the urgency incontinence from the OABSS questionnaire ( r = 0.679; p = 0.044). No correlations existed between the BWT of the DU patients and any of the data from the three questionnaires. Conclusion: The BWT in the DO-DU patients was significantly thicker than that in the DU patients. The DO-DU patients with thicker bladder walls also had higher UDI-6 scores for both urgency and urgency incontinence.